Resin secretory canals in Protium heptaphyllum (Aubl.) Marchand. (Burseraceae): a tridimensional branched and anastomosed system - Palermo, Fernanda Helena [UNESP]; Rodrigues, Maria Ivanildede Araújo [UNESP]; de Nicolai, Juan [UNESP]; Machado, Silvia Rodrigues [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Springer Nature, 2018)
Protium heptaphyllum is a Burseraceae species known by the production of aromatic resin with medicinal, economic, and ecological values. Information on the development, architecture, and lifetime of the secretory system are crucial to understand the resin production and contribute to a more sustainable tapping regime. We investigated the histology and ultrastructure of the secretory canals under a developmental point of view. Stem samples were analyzed under light and transmission electron microscopy by conventional and cytochemical methods. Secretory canals, originated from procambium and cambium, occurred immersed in the primary and secondary phloem. Mature canals have a secretory epithelium and a wide lumen where the exudate is accumulated. A sheath of parenchyma cells with meristematic features surrounds the epithelium. The canals originate by schizogenesis and develop by schyzolysigenesis. Canals active in secretion occurred since the shoot apex and near the cambium. In the dilation zone of the secondary phloem, secretory canals exhibit sclerified epithelial and sheath cells and are inactive in secretion. Secreting epithelial cells have subcellular apparatus consistent with oleoresin, polysaccharides, and enzymes secretion. Pectinase and cellulase were cytochemically detected in developing canals and are involved in cell wall changes associated to canal growth and release of exudate. In P. heptaphyllum, the secretory system has a complex structure resultant from longitudinal growth, lateral ramification, and fusion of the adjacent canals, in addition to intrusive growth of both epithelial and sheath cells. Although some anatomical results are already known, ultrastructural data represent the novelty of this work. Our findings can contribute to the establishment of more efficient and sustainable techniques for resin extraction in this species.
Keywords: Citochemistry; Development; Histology; Secretion; Secretory canal; Ultrastructure